Vulnerability to energy poverty in Portugal: determinants and regional differences - Dietrich, Til (2021)
Despite having a mild climate, Portugal leads the list on excess winter mortality and is among the EU countries with the highest energy poverty level. This study explores which households ’characteristics influence their vulnerability to being energy-poor and checks for regional differences. It employs 2015 HBS data in a logistic regression model, with the expenditure-based 2Mindicator being the dependent variable. The results suggest that, on an aggregate revel, retired, single individuals without children living in a large, rented detached house in a rural area are most vulnerable. Furthermore, there is regional variation along the tested dimensions.